Scientometric Mapping of Copper-Doped Hydroxyapatite Coatings for Biomedical Applications: Knowledge Structure, Collaboration Patterns, and Emerging Research Fronts - Echeverry-Cardona, Laura Maria; Moreno-Vargas, Jhoan Mauricio; Gomez-Aristizaba, Miguel Angel; Santiago, Leonardo Bohorquez; Restrepo-Parra, Elisabeth (Information Research Communications, 2026)
This study presents a scientometric analysis of research on copper-doped Hydroxyapatite (HA-Cu) coatings for biomedical applications covering the period 2004-2025. The aim was to evaluate publication trends, collaboration patterns, thematic evolution, and the intellectual structure of the field. Bibliographic records retrieved from Web of Science and Scopus were cleaned, merged, and analyzed using the Bibliometrix R-package and the Tree of Science (ToS) framework. Bibliometric indicators, including annual scientific production, citation impact, Bradford’s law, Lotka’s law, and collaboration metrics, were computed. Science mapping techniques, including co-authorship and keyword co-occurrence analyses, were applied to identify thematic and relational structures. The results reveal a sustained annual growth rate of 7.64%, with a marked increase in publication activity after 2020. China and India lead in scientific production, while the United States and Japan exhibit higher citation impact. Thematic analysis highlights strong research interest in material modification, biodegradable magnesium substrates, and advanced coating technologies. The Tree of Science model identifies a hierarchical intellectual structure progressing from foundational studies on ion-doped ceramics and biocompatibility toward emerging research fronts involving Plasma Electrolytic Oxidation (PEO/MAO), copper-based nanostructures, and multifunctional implant surfaces. Overall, the study demonstrates that research on HA-Cu coatings has evolved into a consolidated and dynamically expanding interdisciplinary field and provides a structured scientometric framework applicable to related domains in biomaterials and surface engineering.
Keywords: Bibliometric mapping; Bio-medical coatings; Copper-doped hydroxyapatite; Research trends; Scientometric analysis; Tree of Science.